2010
DOI: 10.1007/s00404-010-1654-3
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum intracranial hemorrhage due to unrecognized unilateral moyamoya disease: a case report

Abstract: Moyamoya disease is a rare entity that must be considered in the differential diagnosis of hemorrhagic stroke during pregnancy. It is important to perform careful monitoring and adequate management with cooperation between obstetricians and other specialists when serious complications arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Maruyama et al reported a 41-year-old postpartum woman suffering with sudden onset of dysarthria and left extremity weakness 6 days after delivery, and found protein Z deficiency and a hypercoagulation state which are both significantly associated with ischemic stroke in patients with moyamoya disease ( 21 ). Kakogawa et al reported an antepartum intracranial hemorrhage caused by unilateral moyamoya disease ( 22 ). Park et al reported that severely reduced regional cerebrovascular reserve and frequent transient ischemic attacks at antepartum might present as neurologic deterioration during pregnancy, delivery, and puerperium ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maruyama et al reported a 41-year-old postpartum woman suffering with sudden onset of dysarthria and left extremity weakness 6 days after delivery, and found protein Z deficiency and a hypercoagulation state which are both significantly associated with ischemic stroke in patients with moyamoya disease ( 21 ). Kakogawa et al reported an antepartum intracranial hemorrhage caused by unilateral moyamoya disease ( 22 ). Park et al reported that severely reduced regional cerebrovascular reserve and frequent transient ischemic attacks at antepartum might present as neurologic deterioration during pregnancy, delivery, and puerperium ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occlusive disease of the circle of Willis, known as moyamoya disease, is a relatively rare progressive cerebrovascular disorder, characterized by blocked arteries at the base of the brain and formation of hazy collateral vessels, called moyamoya vessels [1,2]. It is prevalent in Asian countries, especially in Japan [1,3], with 0.4-0.6 cases per 100,000 population [4,5], and it is more prevalent in women than in men.…”
Section: Introductionmentioning
confidence: 99%
“…It is prevalent in Asian countries, especially in Japan [1,3], with 0.4-0.6 cases per 100,000 population [4,5], and it is more prevalent in women than in men. Therefore, we should establish a protocol for the management or anesthesia of pregnant patients with moyamoya disease who undergo cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%